Pengaruh Kompensasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Pt. Purwa Caraka Music Studio Cinere - Khairul Umam; Bacthiar Arifudin Husain (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine how the influence of compensation and Work Discipline on Employee Performance at PT. Purwa Caraka Music Studio partially and simultaneously. This research uses quantitative methods. The sampling technique used saturated sampling and obtained a sample of 60 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The result of the partial compensation variabel (X1) obtained t count > t table (10,602 > 2,002). This means that compesation (X1) has a significant effect on employee performance (Y). statistical test of work thiscipline variable (X2) on employee performance obtained t count > t table (10,714 > 2,002) this means that work discipline has a significant effect on employee performance (Y). simultaneous hypothesis testing obtained F count > F table (85,490 > 3,16). So it can be concluded that the compensation (X1) and work discipline (X2) have a significant effect simultaneously on employee performance (Y). the coefficient of determination is obtained by R square equal to 0,750, meaning that the work environment and work discipline variables together have an influence contribution of 25,% on employee performance. While the remaining 75% is influenced by other factors not examined in this study.